Reconceptualizing Pediatric Strabismus as a Condition Rooted in Sensory Processing Disorder: A Novel Case-Based Hypothesis - Mirjana Bjeloš; Ana Ćurić; Mladen Bušić; Katja Rončević; Adrian Elabjer (Children, 2025)
Background/Objectives: A direct link between sensory processing disorder (SPD) and strabismus has not been systematically investigated, though prior studies suggest sensory modulation may influence visual behaviors. Traditional approaches view strabismus through a binary lens—either normal or pathological motor deviation. This report presents a proof-of-concept case suggesting strabismus may represent a neurobehavioral manifestation of sensory processing imbalance, rooted within the broader framework of SPD. Methods: We report a pediatric case marked by episodic monocular eye closure triggered by environmental stimuli, without identifiable ophthalmologic or neurologic pathology. The child’s symptoms were most consistent with sensory over-responsivity (SOR), a subtype of SPD, manifesting as stimulus-bound monocular eye closure and secondary self-regulatory behaviors. Results: We propose the Fusion Dysregulation Hypothesis, suggesting that exotropia and esotropia represent opposing outcomes along a continuum of sensory connectivity: exotropia arising from neural underwiring (hyporesponsivity and fusion instability), and esotropia from overwiring (hyperresponsivity and excessive fusion drive). Our case, marked by sensory hyperresponsivity, showed frequent monocular eye closure that briefly disrupted but did not impair fusion. This suggests an “overwired” binocular system maintaining single vision despite sensory triggers. In early-onset esotropia, such overconnectivity may become maladaptive, leading to sustained convergence. Conversely, autism spectrum disorder, typically associated with hypoconnectivity, may predispose to exotropia through reduced fusion maintenance. Conclusions: These findings highlight the need for interdisciplinary evaluation. We advocate for structured sensory profiling in children presenting with strabismus and, conversely, for ophthalmologic assessment in those diagnosed with SPD. While our findings remain preliminary, they support a bidirectional screening approach and suggest that sensory modulation may play a previously under-recognized role in the spectrum of pediatric strabismus presentations.